2004
DOI: 10.1211/0022357023259
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of pseudo-ternary diagrams of aqueous mixtures of Quil A, cholesterol and phospholipid prepared by lipid-film hydration and dialysis

Abstract: Pseudo-ternary diagrams for Quil A, phospholipid (phosphatidylcholine (PC) or phosphatidylethanolamine (PE)) and cholesterol were established in order to identify combinations that result in the formation of immune-stimulating complex (ISCOM) matrices and other colloidal structures produced by these three components in aqueous systems following lipid-film hydration or dialysis (methods that can be used to produce ISCOMs). In addition, the effect of equilibration time (1 month at 4 degrees C) on the structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 14 publications
(27 reference statements)
2
16
0
Order By: Relevance
“…Quil A micelles (Fig. 3, white arrow) were also observed in the ISCOM preparations as described in the literature (19,20).…”
Section: Preparation and Characterization Of Posintro™ Formulationssupporting
confidence: 75%
“…Quil A micelles (Fig. 3, white arrow) were also observed in the ISCOM preparations as described in the literature (19,20).…”
Section: Preparation and Characterization Of Posintro™ Formulationssupporting
confidence: 75%
“…This interaction may lower the rigidity of the ring-like subunits, enabling their aggregation to spherical particles in absence of a phospholipid. cholesterol) this was also discussed by Demana et al 28 Moreover, the function of the phospholipid as a fluidiser may become redundant in the cationic cage-like structure as discussed above.…”
Section: Discussionmentioning
confidence: 68%
“…12,28 This method offers the advantage that, unlike in the widely used dialysis procedure, no losses of components are expected, 29 which simplifies interpretation of colloidal structures obtained. It was hypothesized that, if ISCOMs are prepared according to the dialysis procedure, a residual amount of surfactant might at least partially take over the role of the phospholipid, 10 and a recent publication by our group, in which colloidal structures prepared by either the lipid-film hydration method or the dialysis procedure were compared, supported this interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to Morein's earlier studies [16], Dalsgaard et al reported that both Quadri-1 and Quadri-2 formed homogeneous ISCOM matrices when prepared by dialysis. The main difference between the two studies was that Dalsgaard et al included phospholipid in their ISCOM formulation, a component which has recently been shown to be critical for ISCOM formation when crude Quil A is used as the saponin [18]. In another study, the ability of three RP-HPLC purified saponin fractions, designated QH-A, QH-B and QH-C, to form ISCOMs was investigated [19].…”
Section: Introductionmentioning
confidence: 99%